Post Earthquake rise in Amebic Liver Abscesses - Khalid, Abdul; Baqai, Tariq Baqai; Ahmed, Ejaz; Ahmed, Imtiaz (International Journal of Pathology, 2018)
Study the post earth quake incidence of amebic liver abscess in the worst affected area of Muzaffarabad,Azad KashmirStudy Design: Retrospective, descriptive observational study.Place and duration of study: Departments of Medicine and Radiology Abbas Institute of Medical Sciences(AIMS) Muzaffarabad. The study included data from 2001 to 2012.Material and Methods: The records of patients with diagnosis of liver abscess confirmed on ultrasound examinationwere examined.Results: There was 5.5 fold rise in cases of liver abscess following the earthquake. That high incidence remainedstable for three years from 2006 to 2009. It normalized to pre earthquake levels in 2010.Conclusion: Amebiasis is a common and serious infectious disease in developing countries. It should be kept inmind in the differential diagnosis of all cases of pyrexia of unknown origin in catastrophic events with destructionof infrastructure and disruption of water supply systems.